TINJAUAN HUKUM ISLAM TERHADAP IMPLEMENTASI PEMBERIAN MAHAR BERUPA TA’LIM AYAT AL-QUR’AN - Ratna Komala; Misbah Khusurur (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
The aim of this research is to find out about the law of giving dowry in the form of recitation of Al-Qur'an verses in marriage from the perspective of the Shafi'i school of thought and the implementation of giving dowry in the form of recitation of Al-Qur'an verses in marriage. The type of research in this thesis is library research, using a qualitative approach, a research procedure that produces descriptive data in the form of written words that must be observed and analyzed. The method used is to examine the legal review of the dowry ta'lim verses of the Koran and matters related to the implementation of the dowry. From the research it can be concluded that in the Syafi'i school of thought, giving a dowry in the form of recitation of Al-Quran verses is permissible (mubah), because the dowry is a dowry in the form of services that can be paid for so that it is legally valid to be used as a dowry in marriage. The implementation or practice of giving dowry in the form of ta'lim verses from the Koran is as follows: The headman asks the prospective bridegroom about the dowry that will be given. The bridegroom answered the dowry by reciting the verses of the Koran. Then the dowry was handed over in the form of recitation of Al-Quran verses witnessed by many people. After the dowry is handed over, the qobul agreement is then carried out. The qobul consent is completed and closed with a prayer.